Management of Patent Ductus Arteriosus in Term or Near-term Neonates With Respiratory Distress - Yu-Chen Lin; Hsuan-Rong Huang; Reyin Lien; Pen-Hong Yang; Wen-Jen Su; Hung-Tao Chung; Te-Jen Chen; Won-Hsiung Liu (Pediatrics and Neonatology, 2010)
Respiratory distress and patent ductus arteriosus (PDA) in neonates are mutually perpetuating. Contrary to the situation in premature infants, the recognition, clinical relevance and optimal management of PDA in full-term neonates are unclear. The present study aimed to identify PDA as a possible cause of respiratory distress in term and near-term neonates, and to examine the clinical responsiveness of PDA to different treatment modalities in mature-gestational-age neonates. Methods: Patients with gestational ages of over 34 weeks were included in this retrospective chart review; they had PDA as the sole recognizable cause of respiratory distress and were free of all other diseases. Clinical responsiveness to different regimens, including conservative treatment, drug therapy with preload reduction and inotropic agent with or without the addition of indomethacin, and surgical intervention were analyzed. Results: Forty-four neonates qualified for this study. Six received no treatment and their cardiorespiratory symptoms resolved within 1 week (regimen A). Symptoms in 11 neonates were relieved after use of diuretic and inotropic agents (regimen B). Twelve neonates became asymptomatic without further intervention after indomethacin treatment in addition to preload reduction and inotropes (regimen C). A total of 15 of the 44 infants underwent PDA ligation (regimen D) due to persistent heart failure following regimens B or C, but had speedy resolution of respiratory symptoms following surgery. There were significant differences in birth body weight and hemodynamic variation based on left atrium to aortic root dimensional ratio between the treatment (regimens B, C and D) and non-treatment (regimen A) groups (p < 0.05). Conclusion: PDA plays an important role in prolonging respiratory distress in term or near-term neonates. Although most infants respond to noninvasive medical treatment, surgical ligation during the neonatal period is warranted in certain mature infants. Surgical treatment should be considered in patients with smaller birth body weights and those with increased left atrium to aortic root dimensional ratios.